Tuntutan Ganti Rugi dalam Kecelakaan Lalu Lintas - Sulli, Frans A.; Moonti, Roy Marthen; Ahmad, Ibrahim (Lembaga Pengembangan Kinerja Dosen, 2025)
Traffic accidents are events that not only affect physical and material losses, but also cause legal issues in the form of compensation claims. This research aims to comprehensively examine the legal mechanism of compensation claims for victims of traffic accidents in Indonesia, as well as identify obstacles in its implementation. The type of research used is normative legal research, with an approach to statutory provisions, jurisprudence, and other legal documents. The results of the study show that although the legal basis for compensation claims is available, its implementation is still constrained by low legal literacy, complicated evidentiary procedures, and weak institutional support. As a suggestion, regulatory reform, institutional strengthening, and community-based legal socialization are needed to improve victims' access to justice. Thus, the compensation system can run effectively, fairly, and sustainably to protect the rights of traffic accident victims.